Integration of HIV Care with Primary Health Care Services: Effect on Patient Satisfaction and Stigma in Rural Kenya. (7th May 2013) - Odeny, Thomas A.; Penner, Jeremy; Lewis-Kulzer, Jayne; Leslie, Hannah H.; Shade, Starley B.; Adero, Walter; Kioko, Jackson; Cohen, Craig R.; Bukusi, Elizabeth A.
Abstract : HIV departments within Kenyan health facilities are usually better staffed and equipped than departments offering non-HIV services. Integration of HIV services into primary care may address this issue of skewed resource allocation. Between 2008 and 2010, we piloted a system of integrating HIV services into primary care in rural Kenya. Before integration, we conducted a survey among returning adults ≥18-year old attending the HIV clinic. We then integrated HIV and primary care services. Three and twelve months after integration, we administered the same questionnaires to a sample of returning adults attending the integrated clinic. Changes in patient responses were assessed using truncated linear regression and logistic regression. At 12 months after integration, respondents were more likely to be satisfied with reception services (adjusted odds ratio, aOR 2.71, 95% CI 1.32–5.56), HIV education (aOR 3.28, 95% CI 1.92–6.83), and wait time (aOR 1.97 95% CI 1.03–3.76). Men's comfort with receiving care at an integrated clinic did not change (aOR = 0.46 95% CI 0.06–3.86). Women were more likely to express discomfort after integration (aOR 3.37 95% CI 1.33–8.52). Integration of HIV services into primary care services was associated with significant increases in patient satisfaction in certain domains, with no negative effect on satisfaction.